An evaluation of predictors for success of two-duct ligation for drooling in neurodisabilities - Bekkers, Stijn (J Neurol, 2020)
BACKGROUND: Drooling is dependent on various clinical variables. However, while drooling proves refractory to two-duct ligation in 40% of patients, predictors for treatment success are sparse and to date there is little evidence why some respond well while others are non-responders. We aim to find predictors for treatment success and study the effectiveness of two-duct ligation for drooling in neurodisabilities. METHODS: Fifty-four patients with moderate to severe drooling who had undergone two-duct ligation were screened for inclusion. Four patients were excluded due to missing or unreliable primary outcomes. The average age at the time of surgery was 12 years. Predictors were evaluated for treatment success which was defined as ≥ 50% visual analog scale for severity of drooling and/or drooling quotient reduction from baseline. Treatment effect was measured after 8 and 32 weeks compared to baseline. RESULTS: Age (more mature), adequate posture (no anteflexion), and normal speech are predictors for treatment success. Compared to baseline, drooling quotient was significantly lower at 8 (difference 18.6%, 95% confidence interval 12.3–24.9%) and 32 weeks (difference 10.1%, 95% confidence interval 3.9–16.4%). Compared to baseline, visual analog scale was significantly lower at 8 (difference 45.0, 95% confidence interval 37.0–52.9) and 32 weeks (difference 32.9, 95% confidence interval 25.0–40.7). CONCLUSIONS: Age, adequate posture, and a normal speech are predictors for treatment success, are easily determined pre-operatively, and help the clinician providing patient-specific probability of treatment success. There is a significant subjective and objective decrease of drooling after two-duct ligation.